Fragmentation of the mitochondrial network in skin in vivo. - Daniel Mellem; Martin Sattler; Sonja Pagel-Wolff; Sören Jaspers; Horst Wenck; Michael Alexander Rübhausen; Frank Fischer (PLoS ONE)
Mitochondria form dynamic networks which adapt to the environmental requirements of the cell. We investigated the aging process of these networks in human skin cells in vivo by multiphoton microscopy. A study on the age-dependency of the mitochondrial network in young and old volunteers revealed that keratinocytes in old skin establish a significantly more fragmented network with smaller and more compact mitochondrial clusters than keratinocytes in young skin. Furthermore, we investigated the mitochondrial network during differentiation processes of keratinocytes within the epidermis of volunteers. We observe a fragmentation similar to the age-dependent study in almost all parameters. These parallels raise questions about the dynamics of biophysical network structures during aging processes.